Slenderness and mineral fertilization of Pinus caribaea plantations in Cuba - León Sánchez, Maria Amparo; Reyes Pozo, Jorge Luis; Pérez-León, Víctor Ernesto; Bonilla Vichot, Marta; Herrero-Echavarría, Grisel (Instituto de Ecología, A.C., 2019)
The present research studies the slenderness`s answer to fractionated mineral fertilizer application in Pinus caribaea var caribaea Morelet y Golfari plantations on sandy loam soil. The fertilizer formula used was NPK (8-10-10). Seven treatments were established, differenced by fertilizer doses and application regime, alternate and continuous, and an additional witness treatment, without fertilizer. Measures of total height and normal diameter were taken, and the slenderness index was calculated for the 288 analyzed trees at 6 years, 15 years and 35 years of age. At 6 years of age, slenderness mean values were significantly higher with a single doses application of 300 g tree-1 of (NPK); at 35 years of age, the mean was statistically lower than 80 in those treatments with fertilizer doses of 600 g tree-1, 800 g tree-1 or 1000 g tree-1 respectively in alternate regime. These reached the lowest slenderness values. A linear relation between slenderness and diameter at 1,30 m was found in treatments with fertilization and a logarithmic one in the treatment without fertilization. A direct relationship between the proportion of trees with slenderness lower to 80 and the standing trees was found. Individuals with slenderness between 70 and 90 achieved higher wood volume.